The music of topada tindo: the musical composition from the history of Toraja Nobility - Toding, Vernando; Lestari, Dewi Tika; Picanussa, Branckly Egbert (Gelar: Jurnal Seni Budaya, 2024)
This article aims to explore the history of the struggle of the Toraja nobility as a source for the composition of Topada Tindo musical composition.  Reviving the history of Topada Tindo through musical compositions has an important meaning for the Torajan people's struggle to dare fighting against every tyrannical power that oppresses the people. Musical compositions that originate from the history of people's struggles can also functionally continue to revive and preserve positive historical values for each generation. This research uses an art composition method starting from the stage of building ideas from the history of Toraja nobility, exploring themes and theoretical concepts of the work, as well as forming the composition of Topada Tindo musical works. The authors argue that the history of the Topada Tindo struggle is not only a source for the musical composition but can also provide inspiration and guidance for the Torajan people today to faight and kee struggling for well-being. Topada Tindo's musical composition consists of four parts as a description of the musical situation, namely the peaceful situation (part one), the situation of the entry of external cultural influences (part two), the situation of the arrival of Arung Palakka troops (part three), ending with Topada Tindo's resistance (part four). This composition uses the basic notes Bm and C#m, with multimetric 4/4 and 6/8.